Monetary theory - Halm, George N. (Bombay, 1963)
The first edition of this book was published in 1942. The major event in the monetary field since that time has been the Bretton Woods Conference. The intense effort which culminated recently in the establishment of the International Monetary Fund and the Bank for Reconstruction and Development has greatly helped our understanding of the role which money plays in international economic relations. Since it seemed quite obvious that the second edition of Monetary Theory should include these recent developments, the material which is now contained in Part II has been rewritten and greatly enlarged. There are also a few minor additions to Chapters 17 (Section 5) and 23 (Sections 7 and10). Section 4 of Chapter 3 has been simplified.
Keywords: Economic